The Role of Work-Life Balance in Mediating the Influence of Work Environment and Organizational Culture on the Loyalty of Generation Z Employees in Construction Sector Companies in Badung Regency - PUTRA, Putu Ary Krisna; INDIANI, Ni Luh Putu; SURASMI, Ida Ayu (International Journal of Environmental, Sustainability, and Social Science, 2025)
Employee loyalty is an important factor in maintaining organizational stability and productivity, especially for Generation Z, who are now starting to dominate the workforce, possessing unique characteristics in terms of work preferences. This study aims to analyze the role of work-life balance in mediating the influence of the work environment and organizational culture on the loyalty of Generation Z employees in construction sector companies operating in Badung Regency. The population in this study was all Generation Z employees working in construction sector companies in Badung Regency, Bali. The sample used was 100 respondents, determined by a purposive sampling technique based on the Hair formula. The data analysis used in this study is inferential analysis using SEM-PLS. The results of this study indicate that. The work environment has a positive and significant effect on employee loyalty. The work environment has a positive and significant effect on work-life balance. Organizational culture has a positive and significant effect on employee loyalty. Organizational culture has a positive and significant effect on work-life balance. Work-life balance has a positive and significant effect on employee loyalty. The work environment has a positive and significant effect on employee loyalty through work-life balance. Work-life balance partially mediates. Organizational culture has a positive but insignificant effect on employee loyalty through work-life balance. Work-life balance does not mediate (unmediated).